Undergraduates’ Awareness of the Use of Technological Tools for Information Collection and Analysis - Oladele Stephen Gbore; Peter Joy Abosede; Onasanya Samuel Adebisi (Indonesian Journal of Educational Research and Technology, 2024)
The study examined Undergraduates’ awareness of the use of technological tools for information collection and analysis. Specifically, the study is focused on: (i) examining how often final-year undergraduates have heard about the different methods used to collect information about a respondent or participants (ii) investigating how commonly final-year undergraduates believe technological tools are used to collect information (iii) examining how frequently final-year undergraduates have heard about technological tools used to analyze information collected. The sample of the study comprised 100 undergraduates selected using Krejcie and Morgan sample size determination table. The results revealed that the respondents are aware of the common methods (questionnaire, experiment, and interview) used to collect information, except for focused group discussion, which is occasionally used as a method to collect information. Also, it was revealed that the use of computer-assisted tools, social media, and audio-visual tools are common technological tools used to collect information, with low awareness of the use of Google Forms and email. The use of SPSS and Microsoft Excel for information analysis is common amongst undergraduates, which showed high awareness whereas, the use of ACTIVITY INSIGHT, STATA, and NVIVO is not frequent, which showed low awareness. Awareness and practical teachings be organized for undergraduates on the different methods as well as technological tools that can be to collect and analyze information respectively.